Retrospective Thinking: Decolonizing Minerals at National Museums Scotland - Georgina Grant; Ellie Swinbank (Museum & Society)
This paper explores the mineral specimens held by the Science and Technology department at National Museums Scotland (NMS). It examines what these objects and their provenance reveal about the Museum’s collecting methods and how they reflect and perpetuate colonial attitudes in Britain in the nineteenth century. It is informed by recent work moving the Science and Technology collection to new storage, prompting detailed examination of each object and its records.